2016
DOI: 10.1517/17460441.2016.1154037
|View full text |Cite
|
Sign up to set email alerts
|

Resisting resistance: is there a solution for malaria?

Abstract: IntroductionCurrently, widely used antimalarial drugs have a limited clinical lifespan due to parasite resistance development. With resistance continuously rising, antimalarial drug discovery requires strategies to decrease the time of delivering a new antimalarial drug while simultaneously increasing the drug"s therapeutic lifespan. Areas coveredLessons learnt from various chemotherapeutic resistance studies in the fields of antibiotic and cancer research offer potentially useful strategies that can be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 109 publications
0
27
0
Order By: Relevance
“…However, there is serious concern that malaria parasites are developing resistance to this treatment. With parasite resistance continuously rising, anti-malarial drug discovery requires strategies to decrease the time of delivering a new anti-malarial drug while simultaneously increasing the efficacy of existing treatments, developing alternative treatments [42], as well putting in place preventative measures, such as bed nets. In addition to causing serious whole body side effects, these drugs also have the ability to directly affect skeletal and cardiac muscles [43, 44].…”
Section: Anti-malarial Drugs and Their Effects On Cardiac And Skeletamentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is serious concern that malaria parasites are developing resistance to this treatment. With parasite resistance continuously rising, anti-malarial drug discovery requires strategies to decrease the time of delivering a new anti-malarial drug while simultaneously increasing the efficacy of existing treatments, developing alternative treatments [42], as well putting in place preventative measures, such as bed nets. In addition to causing serious whole body side effects, these drugs also have the ability to directly affect skeletal and cardiac muscles [43, 44].…”
Section: Anti-malarial Drugs and Their Effects On Cardiac And Skeletamentioning
confidence: 99%
“…Prolonged administration of it can cause heart block and progressive myopathy [42]. It has also been reported as cause of toxicity, mostly in the retina [45, 46].…”
Section: Anti-malarial Drugs and Their Effects On Cardiac And Skeletamentioning
confidence: 99%
“…As stated by Verlinden et al: "History has clearly indicated that new antimalarials must be continually developed in the ensuing event of resistance development to the current antimalarial arsenal." The occurrence of drug resistance in malaria is significantly faster than the development of antimalarials [3]. Thus, a constant supply of novel unrelated antimalarial compounds with orthogonal modes of action is urgently required.…”
Section: Combinational Therapymentioning
confidence: 99%
“…Despite the effort and funds spent on malaria eradication, it continues to infect approximately 200 million people worldwide every year and kill one in every four infected [2]. While effective in the past, current antimalarials are becoming less and less reliable as the parasite rapidly develops drug resistance [3]. There…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that elevated concentrations of serum total cholesterol and LDL-cholesterol, triglycerides, fibrinogen and platelet count are independent risk factors for CVD [19]. Verlinde et al, (2016) [20] reports that prolonged administration of chloroquine can cause heart block and progressive myopathy. Ikezoe et al, (2009) [22] reports that chloroquine triggers the disruption of lysosomal enzymes, including amyloid-β accumulation and endoplasmic reticulum (ER) stress.…”
Section: Introductionmentioning
confidence: 99%